WHAT CAN WE EXPECT IN THE FUTURE OF ACADEMIC RESEARCH? MOST COMMON RESEARCH PROBLEMS ANALYSED IN THE TOP JOURNALS IN THE FIELD OF ENTREPRENEURSHIP - Đalić, Irena (The European Journal of Applied Economics, 2019)
In the modern era of academic research, it is extremely difficult to define an entirely or largely unexplored research problem. Every researcher is faced with this question in their research. It takes a lot of work and effort to primarily find a topic that is relevant and that will be attractive for study and research. The focus of this paper is research problems related to the field of entrepreneurship. This paper deals with trending research problems over the course of the last five years in the field of entrepreneurship. The survey was conducted with the aim of identifying the least explored areas of entrepreneurship in order to predict future research topics. The methods used to achieve this scientific goal include: description, classification and explanation. By analyzing the sample of 393 papers from the five most cited journals in the field of entrepreneurship, the author came to the conclusion that in the past five years the majority of papers dealt primarily with the topic of innovation and advanced technology, and hardly touched upon the topic of women's entrepreneurship. This paper should help future researchers to select the topics or fields of research in the domain of entrepreneurship.
Keywords: citations; indexed; journals; entrepreneurship